A resource for teaching emergency care communication. (16th July 2015) - Macqueen, Susy; Woodward‐Kron, Robyn; Flynn, Eleanor; Reid, Katharine; Elliott, Kristine; Slade, Diana
Summary: Background: Communication in emergency departments (EDs), often between several health professionals and patients and relatives, is a major cause of patient complaint and error; however, communication‐skills teaching for medical students largely focuses on individual clinician–patient interactions. Context: We developed and implemented an evidence‐informed online resource, Communication for Health in Emergency Contexts (CHEC;http://www.chec.meu.medicine.unimelb.edu.au/resources ) to raise medical students' awareness of the challenges of communication in the ED, and to provide students with communication strategies for addressing these challenges. The foundation of the CHEC resource was the findings and data from a large research project conducted at five emergency departments in Australia over the period 2006–2009. From this, we developed ED scenarios and teaching vignettes using authentic communication data. The project included a nationwide medical curriculum scoping phase, involving interviews with medical students and educators, on ED communication curriculum needs in order to inform the educational activities. Innovation: The CHEC resource provides students with the opportunity to follow real‐life scenarios through all stages of the ED journey, whereas insights from ED medical and nursing staff provide learning opportunities about interprofessional communication for medical students. Evaluation suggests that students find the resource useful, and that the resource has been successfully embedded in medical and junior doctor training on communication and quality and safety. Implications: The CHEC resource enhances the capacity of busy clinical educators to raise students' awareness of the communication needs of emergency health care by focusing on communication in high‐stress, time‐pressured settings using a web format. The CHEC resource provides students with the opportunity to follow real‐life scenarios through all stages of the ED journey